2019
DOI: 10.28982/josam.512779
|View full text |Cite
|
Sign up to set email alerts
|

Relation of peritumoral, prepectoral and diffuse edema with histopathologic findings of breast cancer in preoperative 3T magnetic resonance imaging

Abstract: Aim: Preoperative breast magnetic resonance imaging (MRI) findings can provide rich information about the prognosis of the disease. Morphologic and dynamic features are especially used for it. We aimed to compare peritumoral, prepectoral, and diffuse edema identified in MRI with histopathologic findings, and to show how prognostic information can be gathered from the identification of edema. Methods: We conducted a retrospective cohort study with forty-six women who underwent breast DCE-MRI as part of the pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Edema occurs when excessive fluid accumulates in tissues, either within cells (cellular edema) or within the collagen-mucopolysaccharide matrix distributed in the interstitial space (interstitial edema) [ 13 ]. Uematsu [ 8 ] divided focal breast edema into peritumoral, prepectoral, and subcutaneous types. However, few studies have reported on the pathophysiology of each subtype of focal breast edema.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Edema occurs when excessive fluid accumulates in tissues, either within cells (cellular edema) or within the collagen-mucopolysaccharide matrix distributed in the interstitial space (interstitial edema) [ 13 ]. Uematsu [ 8 ] divided focal breast edema into peritumoral, prepectoral, and subcutaneous types. However, few studies have reported on the pathophysiology of each subtype of focal breast edema.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that peritumoral edema may arise from neoangiogenesis during tumor growth [ 8 14 ]. Increased vascular permeability due to leaky basilar membranes in newly formed tumor vessels can lead to peritumoral proteolysis, resulting in transudation from the intravascular space to the extracellular space, and contributing to peritumoral edema.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations